Analysis of Circulating Haemocytes from Biomphalaria glabrata following Angiostrongylus vasorum Infection Using Flow Cytometry. (25th March 2012) - Barçante, Thales A.; Barçante, Joziana M. P.; Fujiwara, Ricardo T.; Lima, Walter S.
Abstract : Angiostrongylus vasorum is an emerging parasite of dogs and related to carnivores that have an indirect life cycle, with a wide range of terrestrial and aquatic gastropods as the obligatory intermediate host. Unfortunately, the relationship between A. vasorum and their snail hosts remains poorly understood. Circulating haemocytes are the main line of cellular defence involved in the destruction of helminths in snails. Aiming to further characterize the haemocyte subsets in Biomphalaria snails, we have performed a flow cytometric analysis of whole haemolymph cellular components using a multiparametric dual colour labelling procedure. Our findings demonstrated that B. glabrata infected with A. vasorum have two major circulating haemocyte subsets, referred to as small and large haemocytes. Differences in the cell proportion occurred over time. The development of better invertebrate infection control strategies would certainly result in the better control of human diseases caused by other species of the genus Angiostrongylus . Such knowledge will assist in the establishment of novel control strategies aimed at parasites that use molluscs as intermediate hosts and clarify new aspects of the parasite-host relationship regarding cell recognition and activation mechanisms, which are also found in the innate response of vertebrates.